Out-of-pocket expenditure and financial risks associated with treatment of chronic kidney disease in Ethiopia: a prospective cohort costing analysis - Ole Frithjof Norheim; Solomon Tessema Memirie; Mizan Habtemichael; Hamelmal G Hailegiorgis; Leja Hamza Juhar; Tsegay Berhane; Sisay Tesfaye; Workagegnehu Hailu Bilchut; Maekel Belay Woldemariam; Lina Mohammed Ahmedtaha (BMJ Global Health)
Introduction In Ethiopia, most healthcare expenditures are paid out-of-pocket (OOP), while the burden of kidney disease (KD) is rapidly increasing, posing a major public health challenge in low- and middle-income countries, along with a staggering economic burden. We aimed to quantify the extent of OOP health expenditures and the magnitude of associated catastrophic and impoverishing health expenditures (CHE and IHE) for chronic KD (CKD) care in Ethiopia.Methods We conducted a prospective costing analysis for CKD care from the patient perspective. We collected data on OOP health expenditures (2023 US$) and household consumption expenditures from a cohort of 433 patients that were followed prospectively for 6 months. Patients were recruited from six health facilities from four constituencies in Ethiopia. We estimated the burden of OOP payments as the sum of direct medical expenditures (DMEs) and direct non-medical expenditures (DNMEs). DMEs were calculated by summing OOP payments for consultations, diagnostic workups, procedures, medications and hospital stays. DNMEs were computed by totalling OOP expenses for transportation, food and lodging. Additionally, we estimated the economic value of productivity losses incurred by patients and/or caregivers due to time spent seeking care. We used descriptive statistics to measure the extent of CHE and IHE. We ran a logistic regression model to assess the drivers of CHE.Results The mean annual OOP expenditure was US$2337 (95% CI US$2014 to US$2659) and varied by type of care: US$677 (95% CI US$511 to US$825) for outpatient care, US$2759 (95% CI US$1171 to US$4347) for inpatient care and US$5312 (95% CI US$4644 to US$5919) for haemodialysis. DMEs (particularly haemodialysis) were the major drivers of cost, accounting for 76%–85% of the total OOP expenditure. Transportation expenditures were the major contributors among the DNMEs. Among those who sought outpatient, inpatient and haemodialysis care, 36%, 67% and 90% incurred CHE, respectively, at a 10% threshold of annual consumption expenditures. Among all patients, 25.6% of households were impoverished due to OOP medical expenditures, with the rate substantially higher among those requiring haemodialysis (43.4%). Facility type and the type of visit were significantly associated with the odds of incurring CHE (p<0.05), while adjusting for wealth quintile, disease stage, area of residence (urban/rural), family size, patient age and insurance membership status.Conclusions The household economic burden for CKD care is substantial, likely hindering access to necessary treatment and exacerbating the impoverishment, which is prevalent in Ethiopia. This would be an obstacle in achieving universal health coverage and Sustainable Development Goals in Ethiopia.